1996
DOI: 10.1093/ajcp/106.3.378
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity WithinCorynebacterium minutissimumStrains Is Explained by MisidentifiedCorynebacterium amycolatumStrains

Abstract: Korty-eight clinical strains that were tentatively identified as Corynebacterium minutissimum on the basis of standard biochemical reactions (Hollis-Weaver tables) as well as by the use of the API (RAPID) Coryne system were examined further. Two different groups of strains were observed. The first group (including the type strain of C minutissimum) contained 27 strains showing creamy colonies. These strains grew homogeneously in 6.5% NaCl broth, exhibited DNase activity, were susceptible to the vibriocidal com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Our two previously undescribed strains possess mycolic acids, unlike C. amycolaturn, and using the findings of Wauters et al (22), we found that they differ from C. amycolatum by not producing propionic acid. In addition, we found the following differences in the biochemical and morphological properties of the previously undescribed strains and C. amycolatum: the two previously undescribed strains are positive for leucine aminopeptidase activity and degradation of tyrosine and produce colonies with a glistening and creamy appearance, whereas C. amycolatum is negative for leucine aminopeptidase activity and degradation of tyrosine and produces dry colonies (13,22,23). Finally, the results of this study indicate that the two previously undescribed strains should belong to a new species distinct from C. minutissimum and other Corynebacterium species, particularly because of their urease activity, which is one of the key reactions in the identification of corynebacteria.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Our two previously undescribed strains possess mycolic acids, unlike C. amycolaturn, and using the findings of Wauters et al (22), we found that they differ from C. amycolatum by not producing propionic acid. In addition, we found the following differences in the biochemical and morphological properties of the previously undescribed strains and C. amycolatum: the two previously undescribed strains are positive for leucine aminopeptidase activity and degradation of tyrosine and produce colonies with a glistening and creamy appearance, whereas C. amycolatum is negative for leucine aminopeptidase activity and degradation of tyrosine and produces dry colonies (13,22,23). Finally, the results of this study indicate that the two previously undescribed strains should belong to a new species distinct from C. minutissimum and other Corynebacterium species, particularly because of their urease activity, which is one of the key reactions in the identification of corynebacteria.…”
Section: Resultsmentioning
confidence: 98%
“…As determined with the API biotype 100 gallery, the two previously unrecognized strains utilized D-turanose and 3-hydroxybutyrate but not N-acetyl-D-glucosamine, whereas none of 19 C. minutissimum strains exhibited this pattern. In two recent studies of the taxonomy of the genus Corynebacterium, workers reinvestigated the status and identification of C. minutissimum in more detail by using biochemical characteristics and DNA-DNA hybridization since it was demonstrated that there could be confusion with strains of Corynebacterium amycolatum (22,23). As a result, accurate identification of C. minutissimum should be based on a lack of urease, nitrate reductase, a-glucosidase, and P-glucuronidase and the presence of leucine aminopeptidase and tyrosine clearing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Products of glucose fermentation for the taxa shown in Table 2 were analyzed here as described previously (1) or as described in other publications. Vibriostatic disk O129 was applied to most of these taxa for at least one strain, and a zone of 11 to 36 mm was considered to show sensitivity while one of 0 to 10 mm was considered to show resistance (34).…”
mentioning
confidence: 99%
“…C. amycolatum has recently been included in the updated API Coryne database 2.0 (Wauters et al, 1998). The presence of only two reports of C. amycolatum causing endocarditis in the literature may be due to its misidentification, as other non-lipophilic fermentative Corynebacterium species, including Corynebacterium xerosis and Corynebacterium minutissimum, are associated with human disease (Funke et al, 1996a;Zinkernagel et al, 1996). Letek et al (2006) described a molecular method for rapid identification of C. amycolatum from the closely related Corynebacterium striatum, C. minutissimum and C. xerosis, without the requirement for further molecular analysis, based on the use of different primers for amplification of the cell-division divIVA gene using conventional or real-time PCR (Letek et al, 2006).…”
Section: Discussionmentioning
confidence: 99%